The efficiency of two widely used commercial live-traps to develop monitoring protocols for small mammal biodiversity. (July 2016) - Torre, Ignasi; Freixas, Lídia; Arrizabalaga, Antoni; Díaz, Mario
Highlights: Biodiversity monitoring requires protocols for multi-species communities. Small mammal monitoring is based on trapping devices. Longworth and Sherman traps working simultaneously gave similar community results. Both kinds of traps could be used to monitor small mammal diversity. Abstract: Biodiversity monitoring programs have been implemented worldwide as a source of information on ecosystem functioning. However, controversy concerning the indicators that should be monitored, and the development of adequate monitoring protocols for multi-species communities still hamper such implementation, especially in the case of small mammals. We analyze differences in the efficiency of the two most widely used commercial traps (Longworth and Sherman) working simultaneously in eight different mountain habitats in Andorra country (NE Iberia) as a first step for establishing standardized sampling protocols for species-rich small mammal communities. From summer 2008 to fall 2010 (six sampling occasions) we captured a total of 728 small mammal individuals (1445 including recaptures) of 13 species (12 in Longworth and 11 in Sherman, 10 species shared). Despite some specific biases (underestimation of two large species by Longworth traps and underestimation of one small species by Sherman traps), estimates of community parameters and similarity indexes, sampling efficiency (number of small mammals trapped), detectability, mean weight, and sex-ratio of the most abundant species, were similar for both sampling methods. Our results suggested that both trap models could be used interchangeably – without relevant biases – in small mammal community assessments where large species are infrequent. Focussing monitoring programs on highly detectable small mammal species (common species) would allow the establishment of robust monitoring programs aimed at reducing the time invested and economic costs.